2012
DOI: 10.1364/boe.3.001579
|View full text |Cite
|
Sign up to set email alerts
|

In vivo layer-resolved characterization of oral dysplasia via nonlinear optical micro-spectroscopy

Abstract: Optical spectroscopy has proven to be a powerful technique for studying neoplastic transformation in epithelial tissue. Since specific intra-layer precancerous changes originate in the stratified layers of the oral mucosa, layer-resolved analysis will likely improve both our understanding of the mechanism of premalignant transformation, and clinical diagnostic outcomes. However, the native fluorescence signal in linear spectroscopy typically originates from a multi-layered focal volume. In this study, nonlinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 40 publications
4
29
0
Order By: Relevance
“…[108] found redox ratio calculated inversely as NADH/FAD to be increased in cancerous colonic biopsies and malignant cell lines respectively. In vivo studies conducted by Walsh et al in mouse xenograft models for breast cancer [109] and Edward et al in oral cancer models in hamsters [90] also showed similar findings. However a rare exception would be the work of Kirkpatrick et al [29] where the redox ratio (equated as FAD/FAD + NAD(P)H) was found to be increased in high-risk normal tissue and even higher in cancerous ovarian biopsies, as compared to low-risk normal tissues.…”
Section: Metabolic Assessment Of Normal Versus Cancer Cellsmentioning
confidence: 53%
See 2 more Smart Citations
“…[108] found redox ratio calculated inversely as NADH/FAD to be increased in cancerous colonic biopsies and malignant cell lines respectively. In vivo studies conducted by Walsh et al in mouse xenograft models for breast cancer [109] and Edward et al in oral cancer models in hamsters [90] also showed similar findings. However a rare exception would be the work of Kirkpatrick et al [29] where the redox ratio (equated as FAD/FAD + NAD(P)H) was found to be increased in high-risk normal tissue and even higher in cancerous ovarian biopsies, as compared to low-risk normal tissues.…”
Section: Metabolic Assessment Of Normal Versus Cancer Cellsmentioning
confidence: 53%
“…In an in vivo study conducted by Edward et al [90] they observed the normal oral cavity in the hamster to have symmetrically shaped autofluorescence spectra with an emission peak at 515 nm. On the other hand, they observed asymmetric shaped autofluorescence spectra in the dysplastic regions induced by chemical carcinogenesis in hamster oral cavity.…”
Section: Tpef Spectral Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Images were captured using a modified Zeiss confocal laser scanning microscope (LSM 410; Zeiss, Oberkochen, Germany) allowing for SHG microscopy. 22 A near infrared femtosecond laser consisting of a Tsunami Ti:sapphire laser pumped by a frequency doubled Nd:YVO at 532 nm (Spectra Physics, Irvine, CA) served as the illumination source for SHG microscopy. The excitation source for confocal microscopy was an argon/ krypton ion laser capable of providing 488, 568, and 647 nm illuminations.…”
Section: Imaging Protocolmentioning
confidence: 99%
“…The multiphoton microscopy system used for these studies has been reported previously [1] with the modification for microspectroscopy also reported [9]. Illumination for multiphoton autofluorescence excitation was by a Tsunami Ti: Sapphire femtosecond (~100fs, 82MHz) laser (Spectra-Physics, CA) and directed through ultrafast optics into a Zeiss 410 confocal microscope modified for multiphoton microscopy.…”
Section: Multiphoton Systemmentioning
confidence: 99%